The Legacy of German Romanticism in Russian Urban Fantasy - E. A. Safron (Научный диалог, 2020)
The philosophical views of German romantics, as well as images, motives, chronotopes characteristic of German romanticism, embodied in the domestic urban fantasy are analyzed. Special attention is paid to the techniques of the comparative method. The scientific novelty of the research lies in the almost complete absence of works devoted to the study of urban fantasy. It is noted that this fantasy subgenre has not been considered in detail in the context of the continuation of the traditions of romantic German literature. The theoretical basis of the research is presented by the works of M. M. Bakhtin, N. Ya. Berkovsky, V. M. Zhirmunsky, Yu. M. Lotman, S. S. Levochsky, etc. It was revealed that urban fantasy inherits the main images, themes, motives, symbols that dominated in German romanticism: the motive of a double, the image of a doll, an artist, etc. It was established that the authors of urban fantasy not only reproduce the image of a romantic artist-creator, but depict a character-demiurge. It has been proven that urban fantasy deepens and transforms the romantic “night beginning”: the images of the dead and vampires become plot-forming characters in independent series of works. It is concluded that the authors of urban fantasy, like German romantics, activate the readers’ attention to mythology and folklore, creating new fantastic worlds with their help.